Effect of volume of blood cultured on detection of Streptococcus viridans bacteraemia. Issue 5 (May 1984) - Shanson, D C; Thomas, F; Wilson, D
Abstract : Fifty eight patients undergoing dental extraction each had 45 ml blood collected. This was divided into 30 ml and 15 ml blood samples for culture. The 30 ml sample was inoculated into 120 ml nutrient broth with 0.05% liquoid and the 15 ml sample into 60 ml of identical broth so that the final dilution of blood in broth was always 1/5. Bacteraemia due to viridans streptococci was found in 27 and 15 patients by culturing the 30 ml and 15 ml blood samples respectively. Only one further case of streptococcal bacteraemia was detected by culture of the total volume of blood collected (45 ml) rather than culture of the 30 ml blood sample alone. These findings suggest that the culture of 30 ml blood results in the detection of up to 80% more blood cultures yielding Streptococcus viridans than the culture of only 15 ml blood. The collection of more than 30 ml blood for each culture is unlikely to prove worthwhile. It is suggested that 30 ml rather than 15 ml blood is probably the optimal volume of blood for each culture of S viridans when patients with suspected infective endocarditis are investigated.